2021
DOI: 10.1002/cso2.1017
|View full text |Cite
|
Sign up to set email alerts
|

Boolean dynamic modeling of cancer signaling networks: Prognosis, progression, and therapeutics

Abstract: Cancer is a multifactorial disease. Aberrant functioning of the underlying complex signaling network that orchestrates cellular response to external or internal cues governs incidence, progression, and recurrence of cancer. Detailed understanding of cancer's etiology can offer useful insights into arriving at novel therapeutic and disease management strategies. Such an understanding for most cancers is currently limited due to unavailability of a predictive large‐scale, integrated signaling model accounting fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 196 publications
(270 reference statements)
0
8
0
Order By: Relevance
“…Boolean modeling can be applied to those systems where the organization of networks is more important than the kinetic details of the individual interactions [123]. Boolean model in cancer signaling networks can provide holistic models capturing multi-scale, multi-cellular signaling processes involved in cancer incidence and progression [124]. Baur et al [125] modeled different components using Boolean networks in the growth factor signaling pathway to study the efficacy of different drugs in cancer therapies.…”
Section: Modeling Of Cell Signaling Networkmentioning
confidence: 99%
“…Boolean modeling can be applied to those systems where the organization of networks is more important than the kinetic details of the individual interactions [123]. Boolean model in cancer signaling networks can provide holistic models capturing multi-scale, multi-cellular signaling processes involved in cancer incidence and progression [124]. Baur et al [125] modeled different components using Boolean networks in the growth factor signaling pathway to study the efficacy of different drugs in cancer therapies.…”
Section: Modeling Of Cell Signaling Networkmentioning
confidence: 99%
“…EMT-driven BNs can also be used to interrogate the effect of combinatorial therapies to treat cancer, as shown for hepatoma [87]. A recent review has proposed that cancer signaling-driven BNs will be useful for investigating the prognosis of and therapeutic responses to different interventions, contributing to the improvement of the decision-making process in oncology practice [88].…”
Section: Understanding Emt From a Systems Biology Point Of Viewmentioning
confidence: 99%
“…Use of general asynchronous (GA) or random-order asynchronous (ROA) updating scheme permits incorporation of cell-to-cell variability in the BD model of the network while estimating its ability to settle into different phenotypes. 21,25,26 GA updating-based BD model of TNFR1 network unraveled that inhibition of AKT/PKB, 27 RIPK1 28 and FADD 28 are crucial in modulating the steady-state probability of attaining long-term pro-survival responses (attractor). Since GA update scheme could introduce spurious self-loops and bias signal flow paths to prefer a certain entity, the probabilities predicted by these models may not reflect the true extent of the network’s ability to settle into the attractors.…”
Section: Introductionmentioning
confidence: 99%
“…Boolean dynamic (BD) modeling which assumes every node can be either active (ON) or inactive (OFF) circumvents this limitation. 20,21 Boolean model of TNFR1 signaling network using synchronous updating scheme showed that feedback loops involving caspase3 may control culmination into either pro-survival or apoptotic response. 22 Multivalued discrete dynamical simulations, an extension of BD modeling, predicted that hepatocytes and Jurkat-T cells require smac − mimetics for the TNFR1 signaling mediated apoptotic response.…”
Section: Introductionmentioning
confidence: 99%